Social effects of wheeze in childhood: a 25 year follow up. Issue 6853 (5th September 1992) - Ross, S.; Godden, D.; McMurray, D.; Douglas, A.; Oldman, D.; Friend, J.; Legge, J.; Douglas, G.
Abstract : OBJECTIVES–To determine the outcome of childhood wheeze in terms of education, employment, housing, and social class. DESIGN–25 year follow up study. SETTING–Community study based at the department of thoracic medicine, Aberdeen Royal Infirmary. PARTICIPANTS–Three groups of subjects who had been identified in a random community survey in 1964: those who had had asthma in childhood (n = 97), those who had wheezed only in the presence of upper respiratory tract infections (n = 132), and a comparison group who had had no respiratory symptoms as children (n = 131). Subjects were aged 34 to 40 years at the time of the current study. MAIN OUTCOME MEASURES–Interview and questionnaire data on education, employment, housing and social class, ventilatory function, and peak flow rate. RESULTS–Pulmonary function testing showed that only the "asthmatic" group had airways obstruction; this group showed greater peak flow variation than the "wheezy" group, which did not differ from the comparison group. The asthmatic subjects were more likely to have experienced respiratory problems during their school years and associated with their work. Despite these problems, educational attainment, employment, housing, and eventual social class were similar for all three groups. CONCLUSION–Childhood wheeze did not adversely affect education, employment, housing, or social class in this population.